Measuring Success of the Czech Financial Administration before the Supreme Administrative Court: Partial Results of a Quantitative Research of Court Proceedings - Karfíková, Marie; Vojtěch, Jakub (Public Governance, Administration and Finances Law Review, 2019)
The paper discusses the issues of the actions and measures of tax authorities challenged by taxpayers before the administrative justice and thus serves as a contribution to the discussion on efficiency of tax authorities and public administration in general. The authors first address the currently discussed problems of the Czech tax law and tax administration. This is followed by describing their quantitative research focused on answering the question of what is actually the success rate of the Czech Financial Administration before the Supreme Administrative Court in the proceedings on cassation complaints. The ratio of cassation complaints for or against the Financial Administration can be an interesting indicator showing the performance of public administration. Afterwards, it follows an explanation of methodology and presentation of results of the first part of the quantitative research that is focused on analysing the Supreme Administrative Court’s rulings on cassation complaints brought (both by taxpayers or the Financial Administration) against the Regional Courts’ rulings on legal actions against unlawful interference by the Financial Administration with the taxpayers’ rights that cover the period 2013–2017.